‘No one’s gonna tell your story better than you are’: The use of a narrative therapy approach informed by the Tree of Life with children and young people subject to sexual exploitation - Farooq, Romana; Addy, Chelsea; Smyth, Gavin; Appiah, Afua; Kennedy, Patrick J. (Clinical psychology forum (Leicester, England : 2005), 2021)
Child sexual exploitation ‘is a form ofchild sexual abuse where an individual or group… manipulate… a child or young person under the age of18 into sexual activity … in exchange for something the victim needs or wants’ (Department for Education, 2017, p.5). High numbers of cases of child sexual exploitation persists as a growing concern regionally and nationally in England and continues to provide systemic challenges when aiming to effectively reduce risk and harm in at-risk children and young people. At present, ‘best practice fit’ routine interventions are used with children and young people subject to or at risk of sexual exploitation and although these can be effective at reducing harm in the short-term, few interventions have been developed which begin to promote long-term and sustainable positive change in the lives of children and young people (Countryma,n-Roswurm & DiLollo, 2017). Here we outline the use of narrative therapy techniques with children and young people subject to sexual exploitation, in particular the Tree of Life Approa,ch (Ncube, 2006). The provision of a case example on the feasibility and acceptability of this narrative technique is discussed. Keywords: Child sexual exploitation; narrative therapy; Tree of Life.